Combating Terrorism - Jane Marie Bedell (Mankato, MN, United Kingdom COMPASS POINT BOOKS, 2010)
d
Keywords: Peace Justice and Strong Institutions; Criminal Justice & Crime - War On Terror -- Criminal Justice & Crime - War On Terror